O możliwościach czytania dzieła operowego - Wypych-Gawrońska, Anna (Przestrzenie Teorii, 2015)
Elżbieta Nowicka’s book Zapisane w operze. Studia z historii i estetyki opery (Wydawnictwo Poznańskie 2012) [Written in opera. The studies from history and aesthetics of opera] is an attempt to read the ideas, myths and idioms of culture enshrined in works of opera from the 17th to the 20th century. This process of registering takes place on several levels of operatic works: in the librettos, the music and in their staging. It is thanks to these that operas often prove to be the most interesting expression of the presence of myths and ideas in culture, and Elżbieta Nowicka’s book encourages the reader to return to such works.